Evaluating spatial and temporal trends in ecological indicators at dredged material placement sites - Lemasson, Bertrand H.; Tidwell, Kyle S.; Littles, Chanda J.; Carroll, Sean T.; Moritz, Hans R.; Russ, Emily R.; Schultz, Martin T. (Frontiers in Ecology and Evolution, 2025)
The beneficial use of dredged material (BUDM) is increasing and studies have demonstrated ecological benefits, but confidence among stakeholders continues to lag. Primary hurdles for BUDM practitioners lie in identifying approaches that can assuage local concerns, while adopting general metrics to quantify ecological benefits that are transferable and economically feasible. While controlled experiments will advance the practice, managers must first evaluate their portfolio to determine where to focus their efforts. Here we demonstrate how stakeholder feedback and existing data can be combined to provide relatively low-cost, generic evaluations of ecological change at dredge material sites over time that can be communicated to stakeholders and inform future efforts. We evaluated vegetation at 12 sites over 24 years using the normalized difference vegetation index (NDVI) derived from archival satellite imagery. We also leveraged count data from a series of long-term surveys on a local species of concern, the Streaked Horned Lark (Eremophila alpestris strigata), across 10 sites, varying from 8–20 years in duration. Bayesian generalized linear mixed models were fit to both metrics to determine whether they changed over time across a hydrogeomorphic gradient. NDVI showed significant growth over time but maintained relatively low levels (0.04 – 0.38) – a reflection of the dominant vegetation types (sparse shrubs and grasses) and spatial heterogeneity. Parameter significance was evaluated using 68% and 95% credible intervals. Initial NDVI levels were negatively correlated with growth rate, with sites having higher starting levels of NDVI displaying less change over time than those with lower levels. Most Streaked Horned Lark counts remained either steady or increased over time, suggesting relative stability in nesting locations. Neither the NDVI nor lark counts were significantly affected by the hydrogeomorphic gradient. An additional spatially explicit evaluation of associations between lark locations and NDVI values within a recent breeding season revealed a steady increase in potential habitat area along the hydrogeomorphic gradient, extensive potential habitat outside the dredge material placement areas, and potential habitat expansion within the monitored areas. These efforts demonstrate how archival data can be leveraged to quantify historical ecological trends at BUDM projects to improve the practice’s transparency with stakeholders and guide future efforts.